Sosialisasi E-Commerce: Menciptakan Wirausahawan Muda Melalui Teknologi Digital - Darmeinis Darmeinis; Gealsy Ghefira Tsalsabila; Nur Aryaningsih; Muhammad Fahrul Ramdhani; Jihan Aulia Nurjanah; Muhammad Daffanda Fadilla; Arya Hafidz Maulana; Ratna Sari Dewi (FKIP, Universitas Palangka Raya, 2024)
Implementation of the Community Service Activity (PKM) was conducted at SMK Negeri 58 Jakarta, aimed at providing a socialization session on how to become young enterpreneurs by utilizing existing digital technology. The participants of this activity were the students of SMK Negeri 58 Jakarta. The socialization began with a presentation of the material, do practice on how to start becoming young enterpreneurs, then a sharing session about experiences, and concluded with a games related to the material presented. This Community Service Activity (PKM) was positively received by the staff and students of SMK Negeri 58 Jakarta. The event ran smoothly thanks to the enthusiasm of the participants in engaging in each part of the socialization activities.